2009
DOI: 10.1038/ejhg.2009.45
|View full text |Cite
|
Sign up to set email alerts
|

The FAS ligand promoter polymorphism, rs763110 (−844C>T), contributes to cancer susceptibility: evidence from 19 case–control studies

Abstract: The potentially functional polymorphism, rs763110 (À844C4T), in the promoter region of the FAS ligand (FASL) gene, has been implicated in cancer risk, but individually published studies show inconclusive results. To derive a more precise estimation of the association between the FASL rs763110 and risk of cancer, we performed a meta-analysis of 19 published studies that included 11 105 cancer cases and 11 372 controls. We used odds ratios (ORs) and 95% confidence intervals (CIs) to assess the strength of the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 45 publications
(44 reference statements)
0
18
1
Order By: Relevance
“…CM control male, TM tongue cancer male, OM oral cancer male importantly, our study revealed that female carriers of FASL −844 T>C variants (TC and CC) are at twice the risk for buccal mucosa cancer, highlighting heterogeneity and gender-based variations within oral cancer site/tissue and gender-specific research to develop specific treatment modalities. Our finding of association between FASL −844 T>C polymorphism with increased buccal cancer risk is in line with a report [13] but differed from those that suggested protective effect of the polymorphism against oral cancer [14,24]. The variation among the reports may be due to differences in the ethnicity of the subjects, exposure to risk factors, and environment.…”
Section: Discussioncontrasting
confidence: 46%
“…CM control male, TM tongue cancer male, OM oral cancer male importantly, our study revealed that female carriers of FASL −844 T>C variants (TC and CC) are at twice the risk for buccal mucosa cancer, highlighting heterogeneity and gender-based variations within oral cancer site/tissue and gender-specific research to develop specific treatment modalities. Our finding of association between FASL −844 T>C polymorphism with increased buccal cancer risk is in line with a report [13] but differed from those that suggested protective effect of the polymorphism against oral cancer [14,24]. The variation among the reports may be due to differences in the ethnicity of the subjects, exposure to risk factors, and environment.…”
Section: Discussioncontrasting
confidence: 46%
“…Recently, a meta-analysis suggests that the FASLÀ844 C/T polymorphism is associated with cancer risk and the FASLÀ844 C allele is a low-penetrant cancer susceptibility marker for cancer development. A second meta-analysis suggests that the FASLÀ844 T allele has a possible protective effect on cancer risk [18]. The results of subgroup analyses based on ethnicity indicated that the association between the FASLÀ844 T/C polymorphism and the cancer risk was obvious among Asians but not among Caucasians [18,19].…”
Section: Introductionmentioning
confidence: 98%
“…The results obtained by these authors were consistent in that the FAS -1377AA genotype was associated with a significantly increased cancer risk compared to the G/G genotype (14,25). Another meta-analysis of the FASL -844T/C polymorphism in relation to cancer risk was conducted by Zhang et al These authors reported 11,105 cancer cases and 11,372 controls from 19 published studies and concluded that the FASL -844T variant allele was associated with a significantly reduced cancer risk (13). Consistent with these results, our study demonstrated that the individuals carrying the FAS -1377AA or FASL -844CC genotype were at an increased risk for developing breast cancer, which is in agreement with the biological plausibility.…”
Section: Discussionmentioning
confidence: 60%
“…A higher basal expression of FASL is significantly associated with the -844C allele compared with the -844T allele (12). The role of these two functional polymorphisms in carcinogenesis has been extensively studied, and have been shown to be associated with an increased risk of various types of cancer (13,14).…”
Section: Introductionmentioning
confidence: 99%